Climatic changes of temperature, salinity and nutrients in the Amur Bay of the Japan Sea - Yury I. Zuenko; Vladimir I. Rachkov (Известия ТИНРО)
Recent climate-scale (> 3 decades) changes of water temperature, salinity, and concentration of inorganic phosphorus, silicon and nitrogen (nitrites and nitrates) are considered for the Amur Bay where Vladivostok is located ashore. Mean seasonal values of these parameters are determined for the 1980s and 2000s. In summer, the tendencies of climatic scale are noted of SST heightening, temperature at the sea bottom lowering, and nutrients depletion in the upper layer, except of nitrate. In general, the bay becomes more stratified and less productive, on the primary trophic level, but the nitrate income, presumably from atmosphere, prevents the productivity decreasing. Links of the changes with external conditions are analyzed, and the summer monsoon weakening is defined as their main reason that determines weather conditions over Primorye and cross-shelf exchange on its shelf. These processes related with the summer monsoon present the mechanism of large-scale climate changes downscaling to meso-scale level. Besides, there is concluded that the Amur Bay is more vulnerable to marine processes than to terrestrial ones, though it is subjected to the large river discharge.